2003
DOI: 10.1111/1469-8986.00081
|View full text |Cite
|
Sign up to set email alerts
|

Early processing stages are modulated when auditory stimuli are presented at an attended moment in time: An event‐related potential study

Abstract: The present study investigated with event-related potentials whether attending to a moment in time modulates the processing of auditory stimuli at a similar early, perceptual level as attending to a location in space. The participants listened to short (600 ms) and long (1,200 ms) intervals marked by white noise bursts. The task was to attend in alternating runs either to the short or to the long intervals and to respond to rare offset markers that differed in intensity from the frequent standard offset marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
162
2
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(196 citation statements)
references
References 93 publications
30
162
2
2
Order By: Relevance
“…We tested for genotype effects in attention regulation of early auditory processing, as reflected by differences in the amplitude of the P1, N1 and P2 components (e.g., Clark & Hillyard, 1996;Hillyard et al, 1973;Lange et al, 2003;Sanders & Astheimer, 2008). Informed by previous findings (Ceponiene, Westerfield, Torki, & Townsend, 2008) and in line with the scalp topography of the present data (see Fig.…”
Section: Analyses Of Eeg Datasupporting
confidence: 76%
See 2 more Smart Citations
“…We tested for genotype effects in attention regulation of early auditory processing, as reflected by differences in the amplitude of the P1, N1 and P2 components (e.g., Clark & Hillyard, 1996;Hillyard et al, 1973;Lange et al, 2003;Sanders & Astheimer, 2008). Informed by previous findings (Ceponiene, Westerfield, Torki, & Townsend, 2008) and in line with the scalp topography of the present data (see Fig.…”
Section: Analyses Of Eeg Datasupporting
confidence: 76%
“…Early or late auditory evoked potentials have been shown to reflect neural correlates of sensory-driven or conflict-related processes, respectively. We tested whether the two genotype groups differ in attention modulation of sensory processing as reflected in amplitude differences in P1, N1 or P2 component (e.g., Clark & Hillyard, 1996;Hillyard, Hink, Schwent, & Picton, 1973;Lange, Rösler, & Röder, 2003;Sanders & Astheimer, 2008). As for conflict-related processing, we focused on a late negativity occurring approximately in the time window of 450-550 ms after stimulus onset.…”
Section: Aim Of Study and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention can be directed to specific points in time such that people are faster and more accurate given valid than invalid temporal cues (Coull, Frith, Büchel, & Nobre, 2000;Coull & Nobre, 1998;Griffin, Miniussi, & Nobre, 2002;Miniussi, Wilding, Coull, & Nobre, 1999). Furthermore, temporally selective attention has been shown to modulate early auditory processing in a manner similar to spatially selective attention; sounds presented at attended times elicit larger amplitude auditory onset ERP components (Lange, Rösler, & Röder, 2003;Sanders & Astheimer, 2006). However, it is also important to distinguish between auditory selective attention designs in which listeners use a simple feature to determine which sounds they will attend (including the studies cited above) and designs in which listeners are asked to attend to different features while processing the same sounds.…”
Section: Auditory Selective Attentionmentioning
confidence: 99%
“…Intuition suggests that knowing when something will happen helps us to focus resources at that expected point in time to enhance our behavior. By now, many studies indicate that we can use temporal information flexibly and across multiple sensory modalities to orient at-tention selectively to specific intervals (Griffin et al, 2001;Lange et al, 2003;Correa et al, 2004). Positron emission tomography and fMRI studies have shown that control of temporal orienting in speeded-response tasks involves brain areas that participate in spatial orienting of attention as well as areas that participate in motor control (Coull and Nobre, 1998;Coull et al, 2000), including posterior parietal cortex, in which cellular correlates of temporal predictability have been identified (Janssen and Shadlen, 2005).…”
Section: Neural Bases and Modelsmentioning
confidence: 99%